The prospect of utilizing urea-treated maize stover by smallholders in Kenya - Said, A.N.; Wanyoike, M.M. (International Livestock Centre for Africa, 1987)
Outlines the prospect of utilizing urea treated maize stover by smallholders in Kenya. Discusses agricultural activities, such as crop production, animal production, feed constraints, land availability, feed resources, feed conservation and utilization of maize stover.